2020
DOI: 10.1002/jbmr.4324
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Score of Adolescent Idiopathic Scoliosis for Potential Clinical Use

Abstract: Adolescent idiopathic scoliosis (AIS) is a common disease causing three‐dimensional spinal deformity in as many as 3% of adolescents. Development of a method that can accurately predict the onset and progression of AIS is an immediate need for clinical practice. Because the heritability of AIS is estimated as high as 87.5% in twin studies, prediction of its onset and progression based on genetic data is a promising option. We show the usefulness of polygenic risk score (PRS) for the prediction of onset and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…( 36 ) Adding a BMI component to AIS polygenic risk score enhances the sensitivity of the predictive model. ( 3 ) The pleiotropy of rs78148157 suggests that the mechanism is complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 36 ) Adding a BMI component to AIS polygenic risk score enhances the sensitivity of the predictive model. ( 3 ) The pleiotropy of rs78148157 suggests that the mechanism is complex.…”
Section: Discussionmentioning
confidence: 99%
“…(36) Adding a BMI component to AIS polygenic risk score enhances the sensitivity of the predictive model. (3) The pleiotropy of rs78148157 suggests that the mechanism is complex. In this study, we not only demonstrated that rs78148157 is a functional SNP but also identified the transcription factor EGR1, which transactivates the rs78148157-located UNCX enhancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent idiopathic scoliosis (AIS) is a common spinal deformity, and posterior instrumentation and fusion is a common method for treating AIS [ 1 ]. However, the operation is complicated and causes massive intraoperative blood loss (650–2,839 mL) [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) is a common spinal deformity, and posterior instrumentation and fusion is a common method for treating AIS [1].…”
Section: Introductionmentioning
confidence: 99%